2006
DOI: 10.1515/jpem.2006.19.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Alterations of Bone Metabolism in Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Although we did not establish decreased LS2-4 and FN-BMD measurements in patients with DM1, we found reduced bone formation and increased bone resorption markers in children with DM1. Measurements of serum osteocalcin, PINP, urinary Ntx and Ca/Cr might be useful for long-term follow-up in children and adolescents with DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
5
37
1
5
Order By: Relevance
“…Also, our results are in agreement with Bonfanti et al (39) who found that serum CTX in prepubertal children was within normal range at onset of T1DM and decreased during the follow-up to reach a significant difference compared to controls after months of insulin treatment. Confirming results were also found in previous studies (40) but our results came in contrast with Abd El Dayem et al (41) who reported that T1DM diabetics had low BMD after adjustment (Z score), low bone formation and high bone resorption markers. Pubertal subjects (diabetics and controls) have higher BMD and BMC than the prepubertal.…”
Section: Discussionsupporting
confidence: 89%
“…Also, our results are in agreement with Bonfanti et al (39) who found that serum CTX in prepubertal children was within normal range at onset of T1DM and decreased during the follow-up to reach a significant difference compared to controls after months of insulin treatment. Confirming results were also found in previous studies (40) but our results came in contrast with Abd El Dayem et al (41) who reported that T1DM diabetics had low BMD after adjustment (Z score), low bone formation and high bone resorption markers. Pubertal subjects (diabetics and controls) have higher BMD and BMC than the prepubertal.…”
Section: Discussionsupporting
confidence: 89%
“…However, certain of them indicate the presence of discrete bone mineralisation disorders, such as a decrease of bone formation markers and increase of bone resorption markers [28] or lower bone mineral acquisition [5,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, free radicals may increase bone resorption through activation of NF-kB. Several risk factors for osteoporosis, such as smoking [60], hypertension [61] and diabetes mellitus [62,63] are associated with increased oxidative stress. Smoking increases the concentrations of free radicals, which have been suggested to be involved in bone resorption [64].…”
Section: Reactive Oxygen Species and Bone Integ-ritymentioning
confidence: 99%